2017
DOI: 10.1002/anie.201704260
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalyzed Intramolecular Aminations of C(sp3)−H Bonds in Alkylaryl Azides

Abstract: The nucleophilic iron complex Bu N[Fe(CO) (NO)] (TBA[Fe]) catalyzes the direct intramolecular amination of unactivated C(sp )-H bonds in alkylaryl azides, which results in the formation of substituted indoline and tetrahydroquinoline derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(41 citation statements)
references
References 71 publications
0
40
0
1
Order By: Relevance
“…Plietker and his coworkers' study showed that this complex can catalyze intramolecular C(sp 2 )-H and C(sp 3 )-H bond amination reactions of ortho-substituted aryl azides. [84,85] Using 2.5 mol% of [Bu n 4 N][Fe-(CO) 3 (NO)] and with the assistance of microwave, aryl azides bearing ortho-aryl or alkenyl group in 1,2-dichloroethane at 100 o C can be converted to carbazoles and indoles, respectively, in moderate to good yields [84] (Table 21). This reaction was also proposed to have iron imido species as key reactive intermediates.…”
Section: Recent Advancesmentioning
confidence: 99%
See 2 more Smart Citations
“…Plietker and his coworkers' study showed that this complex can catalyze intramolecular C(sp 2 )-H and C(sp 3 )-H bond amination reactions of ortho-substituted aryl azides. [84,85] Using 2.5 mol% of [Bu n 4 N][Fe-(CO) 3 (NO)] and with the assistance of microwave, aryl azides bearing ortho-aryl or alkenyl group in 1,2-dichloroethane at 100 o C can be converted to carbazoles and indoles, respectively, in moderate to good yields [84] (Table 21). This reaction was also proposed to have iron imido species as key reactive intermediates.…”
Section: Recent Advancesmentioning
confidence: 99%
“…[86][87][88][89][90] Accordingly, the [Bu the C(sp 2 )-H bond amination reactions. [85] The subtle difference is having higher temperature (120 o C vs. 100 o C), and the use of a mixed solvent of DMF with ClCH 2 CH 2 Cl. Under optimized conditions, the tertiary, secondary, and even primary β-C(sp 3 )-H bonds on ortho-alkyl substituted aryl azides successfully undergo amination reactions, giving indoline and tetrahydroquinoline derivatives in moderate yields (Table 22).…”
Section: (No)]mentioning
confidence: 99%
See 1 more Smart Citation
“…We initiated this project by employing the reaction conditions that proved successful in the intramolecular C–H‐aminations using aryl azides …”
Section: Optimization Of Fe‐catalyzed C(sp2)–h‐aminationmentioning
confidence: 99%
“…[7] Furthermore, intramolecular, Pd-catalyzed a-arylations of N-aryl-b-alanine derivatives have been reported. [8] Moreover,p hotocatalytic cyclizations of 3-(iodoethyl)indoles with acrylonitrile, [9] iron-catalyzed CÀH-activation of ortho-alkylarylazides, [10] and samarium-diiodide induced Barbier-type cyclizations of N-(4-oxoalkyl)indole derivatives have been reported. [11] The most prominent reactiont oa ccess indole derivatives is the Fischer indolization of arylhydrazones, [12] that starts from the hydrazone, which is under acidic conditions in equilibrium with enamine 5 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%